2019
DOI: 10.13057/biodiv/d200228
|View full text |Cite
|
Sign up to set email alerts
|

Pathognomonic features and ultrastructural of Koi Herpesvirus infected Oreochromis niloticus

Abstract: Abstract. Wahidi BR, Yanuhar U, Fadjar M, Andayani A. 2019. Pathognomonic features and ultrastructural of Koi Herpesvirus infected Oreochromis niloticus. Biodiversitas 20: 497-503. Koi Herpesvirus (KHV) has caused considerable losses in the cultivation of the Cyprinidae family worldwide. In addition to infecting Cyprinidae, KHV can also infect other freshwater fish. This study reports histopathology and ultrastructural analysis of KHV that infect Nile tilapia. Although there are no specific clinical symptoms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…d. Encouraging various parties to increase their ability and willingness to develop, managing, and updating data and information content on an ongoing basis so that what is needed by related parties is available in real-time. Wahidi (2019) concluded that E-Government is a form of application for carrying out tasks and governance using telematics technology or information and communication technology. E-Government applications provide opportunities to improve and optimize relations between government agencies, the relationship between the government and the business world and society.…”
Section: E-government Development Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…d. Encouraging various parties to increase their ability and willingness to develop, managing, and updating data and information content on an ongoing basis so that what is needed by related parties is available in real-time. Wahidi (2019) concluded that E-Government is a form of application for carrying out tasks and governance using telematics technology or information and communication technology. E-Government applications provide opportunities to improve and optimize relations between government agencies, the relationship between the government and the business world and society.…”
Section: E-government Development Strategymentioning
confidence: 99%
“…E-Government applications provide opportunities to improve and optimize relations between government agencies, the relationship between the government and the business world and society. The mechanism for this relationship is through information technology, a collaboration or merger between computers and communication network systems (Wahidi et al, 2019). E-Government Technology has caused much bureaucracy to be reorganized.…”
Section: E-government Development Strategymentioning
confidence: 99%
“…In an another report the morphology of KHV virus was simply divided into enveloped and non-enveloped virion (Dong et al, 2011). Ultrastructural analysis of gill tissues sampled from KHV infected Nile tilapia found that viral particles with a diameter of 150-170 nm in the cytoplasm or outside the gill cells (Wahidi et al, 2019) . Different size of capsids or virion particles in diameter in above researches probably due to the different cutting side of section or different stages of virus development but the morphologies were similar and consistent with viruses from the Herpesviridae family.…”
Section: Morphology Of Cell Line Infected With Khv Gy01 By Electron Mmentioning
confidence: 99%